Adverse Events Associated with Balloon Sinuplasty: A MAUDE Database Analysis. (22nd October 2019) - Hur, Kevin; Ge, Marshall; Kim, Jeehong; Ference, Elisabeth H.
Abstract : Objective: Balloon sinuplasty utilization has increased significantly since its introduction over a decade ago. However, the most common associated complications are still unknown. The objective of this study was to analyze adverse events related to balloon sinuplasty. Study Design: Retrospective cross‐sectional analysis. Setting: Food and Drug Administration's MAUDE database (Manufacturer and User Facility Device Experience; 2008‐2018). Subjects and Methods: The MAUDE database was searched for all reports on adverse events involving balloon sinuplasty devices from the 3 leading manufacturers: Acclarent, Entellus, and Medtronic. Reported events were reviewed and categorized. Results: During the study period, there were 211 adverse events from 208 reports divided into the following categories: patient related (n = 102, 48.3%), device related (n = 101, 47.9%), and packaging related (n = 8, 3.8%). Four periprocedural deaths were reported but were not clearly associated with technical complications. The most common device‐related complications were guide catheter malfunction (39.6%), balloon malfunction (38.6%), and imprecise navigation (17.8%). The most common patient‐related complications were cerebrospinal fluid leak (36.3%), eye swelling (29.4%), and epistaxis (11.8%). A lateral canthotomy was performed in 30.0% of eye‐swelling complications. Sixty percent of eye complications occurred during balloon dilation of the maxillary sinus. The years 2014 (n = 48) and 2012 (n = 32) had the highest number of adverse events reported as compared with all other years. Conclusion: The most common adverse events associated with balloon sinuplasty include balloon malfunction, guide catheter malfunction, cerebrospinal fluid leak, and significant eye swelling. Health care providers should discuss these possible complications when consenting patients for balloon sinuplasty.